The cry of the earth and the cry of the poor: hearing justice in John's gospel - Rushton, Kathleen P. (SCM Press, 2020)
"Despite the explicit proclamation in John's Gospel of the 'Word made flesh' it is hard to hear or preach such an esoteric Gospel in a way which offers something concrete, relevant and timely for congregations. Focused around the lectionary readings from the Gospel, "The Cry of the Earth and the Cry of the Poor" suggests that far from being a Gospel which sits at a safe remove from every day life, it can in fact be preached and read as an urgent call to hear the voices of the oppressed in our world. Encouraging preachers and those in the pews to engage in the ancient practice of lectio divina, the book offers an accessible resource to help address the divorce between what is heard from pulpit, and the urgent social and ecological justice concern of our times"--Back cover